Host institutions in compliance with the principle of exceptionality (Research, Society and Development, 2021)
This article deals with the institutionalization and care process, which was changed after the creation of the Child and Adolescent Statute (ECA) and the Adoption Law, making institutional care a protective measure in order to prevent the rights of children and adolescents are violated. For many years, the situation of these subjects was totally different, they applied correction and punishment measures, taking into account poverty. However, with the emergence of new laws, full protection was instituted, being the duty of the family, society and the State to guarantee absolute priority regardless of the social class to which they belong. In addition, institutional care must be exceptional and temporary, bearing in mind that the child or adolescent can only be removed from the family and social life, after all possible measures have been used. Removal from family life should be a rare measure, preventing developmental damage caused by separation. From this, the objective was to carry out a study on the aspects of exceptionality and provisionality in situations of child and adolescent care, in compliance with the principle of full protection. In order to achieve this objective, the deductive and explanatory method was used through a qualitative bibliographic research. Finally, it is considered that there is a failure to observe the fundamental rights of the child/adolescent and the principles of exceptionality and provisionality, hurting what is intended as the main objective, that is, family life and full development.